2012
DOI: 10.4244/eijv7i9a174
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes based on completeness of revascularisation in patients undergoing percutaneous coronary intervention: a meta-analysis of multivessel coronary artery disease studies

Abstract: In patients with multivessel coronary disease, complete revascularisation with PCI may be associated with better outcomes than incomplete revascularisation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…However, the retrospective nature of those studies, the small number of patients enrolled, the lack of consensus on CR definition, numerous statistical and methodological issues, and significant differences in patient populations studied has led to conflicting results as to the prognostic importance of CR. Recently, Aggarwal and colleagues showed in a meta-analysis from 9 studies that CR by PCI was associated with a marginally lower rate of death, MI, and need for CABG at a mean follow-up of 29 months, with no difference in repeat PCI, as compared with IR (28). Conversely, the only randomized controlled trial comparing a strategy of culprit vessel revascularization to CR failed to demonstrate superiority of CR compared with IR regarding 30-day and 1-year rate of major outcomes, including mortality (29).…”
Section: Discussionmentioning
confidence: 99%
“…However, the retrospective nature of those studies, the small number of patients enrolled, the lack of consensus on CR definition, numerous statistical and methodological issues, and significant differences in patient populations studied has led to conflicting results as to the prognostic importance of CR. Recently, Aggarwal and colleagues showed in a meta-analysis from 9 studies that CR by PCI was associated with a marginally lower rate of death, MI, and need for CABG at a mean follow-up of 29 months, with no difference in repeat PCI, as compared with IR (28). Conversely, the only randomized controlled trial comparing a strategy of culprit vessel revascularization to CR failed to demonstrate superiority of CR compared with IR regarding 30-day and 1-year rate of major outcomes, including mortality (29).…”
Section: Discussionmentioning
confidence: 99%
“…However, it remains to be determined whether complete or incomplete revascularization, non-IRA intervention, and timing of intervention can be improved. Although recent studies have supported complete revascularization in patients, including those with angina,36)37)38) more studies are needed to establish staged PCI in these patients.…”
Section: Real-world Application Of Multivessel Intervention In Patienmentioning
confidence: 99%
“…In patients with MVD, complete revascularization (CR) with PCI may be associated with better outcomes than incomplete revascularization (IR). A recent meta-analysis [15] of 9 PCI studies (7 with BMS, 1 with DES, and 1 with both) demonstrated that patients undergoing CR compared to IR had significantly lower risk of mortality (RR, 0.82; 95% CI, 0.68 to 0.99; p = 0.05). Also in a large (1400 patients) DES study [16] not included in the meta-analysis [15], patients with IR had a strong tendency toward higher risk of death than those with CR over 5 years (8.8% versus 6.2%; p = 0.057).…”
Section: Contents Lists Available At Sciverse Sciencedirectmentioning
confidence: 94%